(untitled) (Revista Cientifica Ingenio Magno, 2022)
Internet of Things (IoT) allows to interconnect and to interchange objects data through Internet. This component is part of a global term denominated Industry 4.0 that involved cyber-physical components for automation in industry. But IoT can be applied to different fields in research and technological developing as laboratory automation. Thus, it was developed a system that measure and classify pins used on Tail Pinch Test automatically. Our objective was to create a system that allow to categorize automatically instruments that are used in experiments. Thus, measurements variations are reduced, and the reliability of experiments grows. The system was based on Arduino ADK and resistive sensor to acquire pressure data. Also, a WIFI network and cloud computing service was used in the system. The application layer processed 100 pressure measurements and classified in linguistic values a pin using an Artificial Neural Network.